Psychological implications and rehabilitation programmes due to football‐related injuries. Issue 4 (31st July 2021) - Borg, Anthea Fernanda; Falzon, Ruth; Muscat, Adele
Abstract: Background: This research explored the experience of footballers who had experienced a sports‐related injury and sought psychological and/or counselling support. What interventions did athletes find helpful/not helpful for coping with such an experience? Method: Drawing upon the principles of phenomenology, hermeneutics, and ideography, interpretative phenomenological analysis (IPA) was used to provide insight into the athletes' experiences and their personal perceptions of the injury. Semi‐structured interviews with six Maltese top‐level football players who have sustained and overcome a sports‐related injury were used for the collection of data. Findings: The athletes' appraisals of their injury were explored, and their attitudes towards the different forms of support received and the psychological interventions used were identified. Despite the psychological support sought and received on a personal level, the participants suggested that their mental health was often overlooked by their clubs, leaving them with feelings of helplessness and insecurity. Recommendations: Recommendations, which can be adopted to create sports environments that promote athletes' psychological well‐being, are presented. These include recruiting professional service providers such as counsellors and sport psychologists within clubs, as well as the promotion of such services to diminish the stigma around athletes' mental health. Since sport psychologists usually focus on sports' performance enhancement, it may be wise for clubs to create transdisciplinary teams, which include other health professionals, such as counsellors, for more in‐depth one‐to‐one counselling related to readiness to play. This suggests the implementation of holistic sport education programmes promoting mental well‐being. Recommendations for further research are also discussed.